E-learning system application for physical education and sports specialist training - Barakhsanov, V. P.; Barakhsanova, E. A.; Olesov, N. P.; Prokopyev, M. S. (Theory and Practice of Physical Culture, 2018)
The study analyzes the potential benefits of the e-learning system for future physical education and sport specialists. Subject to the study were the Physical Culture and Sports Institute students and masters majoring in Pedagogical Education at Ammosov North-Eastern Federal University. The study data shows the need for an electronic information and educational system to be applied to improve the physical education process. The study subject is highly topical due to the need for a theoretically grounded, practically tested and applicable in the Russian physical education system curriculum to make future teachers knowledgeable and skillful in the e-learning technologies (ELT) applicable in their professional service. The methods applied for the study purposes were academic progress tests, experimental tools and mathematical methods of statistics. The study data and analyses showed benefits of the proposed physical education and sport specialist training model with the modern e-learning technologies to support professional careers, with the model benefits verified by the students` progress in the e-learning technologies.